(untitled) (International Journal of Engineering and Computer Science, 2013)
- This paper presents the study of 3D Internet in web 3.0 and analyze how it is used in present and future. 3D internet also known as virtual worlds is a powerful new way for you to reach consumers, business customers, co-workers, partners, and students. It combines the immediacy of television, the versatile content of the Web, and the relationship-building strengths of social networking sites like Face book. Yet unlike the passive experience of television, the 3D Internet is inherently interactive and engaging. Virtual worlds provide immersive 3D experiences that replicate (and in some cases exceed) real life. Second Life is one such resource which is implementing the concept of the 3D Internet in its applications. And off late this application has been a great success in the United States and is expected to affect the internet usage in a drastic way. This paper is for anyone who may have recently heard the term "3D Internet in web3.0" for the first time and needs to know what it is and how it helps them.